2001
DOI: 10.1002/mrd.1120
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis in sea urchin oocytes, eggs, and early embryos

Abstract: Certain experimental manipulations with sea urchin oocytes, eggs, and early embryos result in induction of cell death. We were interested in whether or not these cells possessed functional apoptotic machinery, and whether cellular demise under certain experimental conditions is due to activation of a programmed cell death pathway. Therefore, we evaluated a number of apoptosis assays in sea urchin oocytes, eggs, and early embryos experimentally induced to apoptose with staurosporine. Our results indicate that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
33
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 16 publications
(13 reference statements)
3
33
0
Order By: Relevance
“…When the results of the TUNEL assay are examined it is apparent that some cells, a significantly lower percentage, are apoptotic without having been exposed to UVR. A functional apoptotic pathway has previously been shown in sea urchin embryos and larvae (Voronina and Wessel, 2001;Roccheri et al, 2002) and the results reported here for green sea urchin embryos reveal a significant increase in the number of apoptotic cells after exposure to UVR. While the work of Voronina and Wessel (2001) suggests that the TUNEL assay may underestimate the number of apoptotic cells, we feel that this underestimation would be systematic throughout our experiments and thus not affect the interpretation of UVR-induced apoptosis in the treatments described above.…”
Section: Discussionsupporting
confidence: 80%
“…When the results of the TUNEL assay are examined it is apparent that some cells, a significantly lower percentage, are apoptotic without having been exposed to UVR. A functional apoptotic pathway has previously been shown in sea urchin embryos and larvae (Voronina and Wessel, 2001;Roccheri et al, 2002) and the results reported here for green sea urchin embryos reveal a significant increase in the number of apoptotic cells after exposure to UVR. While the work of Voronina and Wessel (2001) suggests that the TUNEL assay may underestimate the number of apoptotic cells, we feel that this underestimation would be systematic throughout our experiments and thus not affect the interpretation of UVR-induced apoptosis in the treatments described above.…”
Section: Discussionsupporting
confidence: 80%
“…Activation of caspases in sea urchins has also been reported for embryos exposed to staurosporine (Voronina and Wessel, 2001). These authors observed differences in apoptotic response between oocytes, eggs and early sea urchin embryos, suggesting that activation of apoptotic pathways may differ depending on the developmental stage.…”
Section: Discussionmentioning
confidence: 68%
“…The effect on cell viability can be explained by the fact that eIF4E-binding peptides were linked to the penetratin peptide-carrier sequence, which mediates the rapid transport of peptides across cell membranes. Sea urchin eggs possess functional apoptotic machinery (Voronina and Wessel, 2001). Yet, the microinjection of 4E-BP peptide into unfertilized sea urchin eggs did not affect cell viability.…”
Section: Discussionmentioning
confidence: 99%